Rapid and simple molecular tests for the detection of respiratory syncytial virus: a review. (3rd July 2018) - A. Hogan, Catherine; Caya, Chelsea; Papenburg, Jesse
ABSTRACT: Introduction : Respiratory syncytial virus (RSV) is a leading cause of acute respiratory infections. The clinical manifestations of RSV are indistinguishable from other etiologies of acute respiratory infection. Therefore, accurate and timely laboratory testing is needed to impact clinical management. There are now multiple rapid, low-complexity, commercially available assays for RSV. These tests present significant performance advantages compared to older antigen detection tests. Accurate and rapid diagnosis of RSV has the potential for enabling timely cessation of unnecessary antibiotics and implementation of good infection control practices. Furthermore, a recently approved RSV diagnostic assay can reduce the test turnaround time to 13 min or less. Areas covered : The authors aim to review the importance of rapid and accurate testing for RSV and will describe the available molecular RSV diagnostic assays approved for use at the point-of-care. Expert commentary : Further independent evaluations are needed to confirm that the accuracy of the low-complexity assays is indeed similar to reverse transcriptase polymerase chain reaction across the age spectrum, and in immunosuppressed hosts. In the future, the challenge will be to achieve a balance between increasingly sophisticated multiplex diagnostic platforms and tests that are sufficiently simple to be used at the point-of-care.